Azido‐Substituted BODIPY Dyes for the Production of Fluorescent Carbon Nanotubes. Issue 43 (24th August 2015) - Fedeli, Stefano; Paoli, Paolo; Brandi, Alberto; Venturini, Lorenzo; Giambastiani, Giuliano; Tuci, Giulia; Cicchi, Stefano
Abstract A series of azido‐dyes were synthesized through Knoevenagel reactions of an azido‐BODIPY with aromatic aldehydes. The nature of the substituents allowed the fine tuning of their spectroscopic properties. The dyes were used to decorate oxidized multiwalled carbon nanotubes (ox‐MWCNTs), bearing terminal triple bond groups, by CuAAC reactions, affording fluorescent materials. This decoration allowed the efficient determination of the internalization of the ox‐MWCNT derivatives by different model cancer cells, such as MCF7.